THE USE OF CODE SWITCHING IN YOU AND INSECURITIES (2023) NOVEL BY AYYA - Anggraeni, Mesfari Dwi; Riyono, Ahdi; Rusiana, Rusiana (CALL, 2024)
This study aimed to identify the codes used, the types, and the reasons of the use of code switching found in the conversational expression in You and Insecurities novel by Ayya. The researcher analyzed the types of code switching using the theory proposed by Poplack (1980) and the reasons of code switching based on the Hoffmann’s (1991) theory. The findings showed that the characters employed three languages in the conversations, those are Indonesian, English, and Sundanese. The most frequent types of code switching found is inter-sentential switching. It can be seen that the characters in the novel have good English skill because they have the ability to intentionally switch the language from Indonesian to English and vice versa. The most frequent reasons of code switching found is talking about particular topic. The characters employed code switching in their conversation to talk or discuss a certain topic because they feel free and comfortable to express their feelings and to make the communication easy to understand. By analyzing the codes, the types, and the reasons of code switching found in You and Insecurities novel using sociolinguistics theories, the researcher realized that a sociolinguistics approach can reveal how language in a novel reflects different social groups, the dialects and languages used by the characters, and how the social and cultural context influences the narrative. The communication style of urban people of Jakarta, in particular of the young executive group identity, is reflected in the studied novel that is You and Insecurities by Ayya. Keyword: bilingualism, multilingualism, code switching, novel